AB0687 SPHINGOSINE 1-PHOSPHATE AND ITS RECEPTOR AS BIOMARKERS AND ACTIVITY PARAMETERS IN RHEUMATOID ARTHRITIS - Mendoza Mendoza, D. V.; Ruiz-Montesino, D.; Dominguez, C.; Bocio, J.; Giner García, M.; Vázquez Gómez, M. A.; Montoya García, M. J.; Pérez Venegas, J. J. (Annals of the rheumatic diseases, 2024)
Background:Sphingolipids are complex lipids that are metabolised to form signalling molecules. Sphingosine-1-phosphate (S1P) is a bioactive lipid that is produced by the phosphorylation of sphingosine and is involved in cell chemotaxis, migration, growth and proliferation (1).S1P is involved in rheumatoid arthritis (RA) directly, through proinflammatory cytokine synthesis and increasing mononuclear cell recruitment, mediated by TNF-alpha and IL-1, and indirectly, through binding to its receptors, increasing T lymphocyte (LT) recruitment and migration and decreasing LTreg levels. Locally, high levels of S1P lead to a decrease in S1PR1 and therefore the effect of S1P is futher increased, maintaining the presence of LT at the synovial tissue (2).Objectives:To assess S1P levels and its receptor, S1PR1, in RA patients and their role as markers of activity in early and established RA.Methods:54 patients with RA from the rheumatology outpatient clinic of the Hospital Virgen Macarena were included. 26 patients had early RA (< 1 year of evolution) and 28 had established RA (≥ 1 year of evolution) and 21 healthy controls matched for age and sex. Demographic, clinical, laboratory, treatment and activity index (DAS28 CRP) data were collected. S1P and S1PR1 serum levels were determined by ELISA. Hands and feet evaluation by ultrasound (US) was performed, according to the EULAR/OMERACT protocol. Statistical analysis was performed with a significance level of less than 0.05. The study was approved by the Hospital Ethics Committee.Results:Most of the RA patients were female, 87% (n 47), with mean age of 52,5 (±13,1) years and mainly RF-positive (82%). The mean DAS 28 was 3,17 ± 1,51, with a median of 2,98 (0,69-6,79) for established RA and 3,32 (1,35-6,82) for early RA sub-groups. The percentage of the patients that were on treatment with classical disease-modifying drugs was 75,93% for the group of all RA patients, 73,08% for patients with early RA and 78.57% of those with established RA.27,78% of total RA were on biologics or synthetic targeted drugs, being more frequent in established RA (50%) than in early RA (3,85%).S1P and S1PR1 levels were higher in all RA groups, although without statistical significance for S1P in early RA sub-group (Graph 1). When comparing S1P and S1PR1 levels in patients with recent-onset RA versus those with established RA, no significantly differences were found, with median levels of S1P 102,43 vs 119,5 and S1PR1 2,76 vs 3,44 (p>0,05) respectivelyNo statistically significant correlation was found between S1P and S1PR1 and activity assessed by DAS28 CRP (p= 0,226 and p=0,862 respectively)S1PR1 levels were significantly higher in patients without Doppler activity versus Doppler activity one (3,35 vs 3,16, p=0,02). This was also confirmed in the established RA sub-group (3,42 vs 3,09, p=0,03) (Graph 2). This association was not found for S1P levels.A weak negative correlation between S1PR1 levels and Doppler activity in hands (r=-0.458) (p= 0.019) and with Doppler activity in hands and feet together (r=-0.462) (p= 0.035), measured by total Doppler US index, was found.Conclusion:Serum levels of S1P and S1PR1 are elevated in RA patients compared to control subjects and may be considered as biomarkers with diagnostic value.Elevated S1PR1 levels in RA patients are associated with lower activity assessed by Doppler US and may be a complementary marker of activity.The low clinical activity of the patients in our study may explain the lack of correlation between S1P and S1PR1 levels and DAS28 CRP.More and larger studies are needed to obtain conclusive data.REFERENCES:[1] Gomez-Larrauri A, Presa N, Dominguez-Herrera A, Ouro A, Trueba M, Gomez-Munoz A. Role of bioactive sphingolipids in physiology and pathology. Essays Biochem. 2020;64(3):579–89.[2] Pérez-Jeldres T, Alvarez-Lobos M, Rivera-Nieves J. Targeting Sphingosine-1-Phosphate Signaling in Immune-Mediated Diseases: Beyond Multiple Sclerosis. Drugs [Internet]. 2021 Jun;81(9):985–1002Graph 1.Comparison of S1P and S1PR1 median levels between RA groups and control group (*p<0,05, **p<0,01)Graph 2.Comparison of S1PR1 median levels between RA patients with and without Doppler activity (*p<0,05)Acknowledgements:NIL.Disclosure of Interests:None declared.